Trends in biopolymer science applied to cosmetics - Mendoza‐Muñoz, Néstor; Leyva‐Gómez, Gerardo; Piñón‐Segundo, Elizabeth; Zambrano‐Zaragoza, María L.; Quintanar‐Guerrero, David; Del Prado Audelo, María Luisa; Urbán‐Morlán, Zaida (International journal of cosmetic science, 2023)
The term biopolymer refers to materials obtained by chemically modifying natural biological substances or producing them through biotechnological processes. They are biodegradable, biocompatible and non‐toxic. Due to these advantages, biopolymers have wide applications in conventional cosmetics and new trends and have emerged as essential ingredients that function as rheological modifiers, emulsifiers, film‐formers, moisturizers, hydrators, antimicrobials and, more recently, materials with metabolic activity on skin. Developing approaches that exploit these features is a challenge for formulating skin, hair and oral care products and dermatological formulations. This article presents an overview of the use of the principal biopolymers used in cosmetic formulations and describes their sources, recently derived structures, novel applications and safety aspects of the use of these molecules. Résumé Le terme biopolymère fait référence aux matériaux obtenus par modification chimique des substances biologiques naturelles ou ceux qui surviennent des processus biotechnologiques. Ils sont biodégradables, biocompatibles, et non‐toxiques. Du à leur avantages, les biopolymères ont de larges applications dans les cosmétiques conventionnels ainsi que dans les nouvelles tendances, et se placent comme des ingrédients essentiels qui peut être utilise comme modificateurs rhéologiques, émulsifiants, producteurs de films, humectants, hydratants, antimicrobiens, et, plus récemment, comme matériaux avec activité métabolique sur la peau. Le développement d'approches compte tenu de ces caractéristiques constitue un défi pour la création de produits de soins capillaires, dermatologiques et buccodentaires. Cet article présente une vision sur l'utilisation des principaux biopolymères dans les produits cosmétiques, et décrit leurs sources, leur structures dérivées, les nouvelles applications, ainsi que les aspects de sécurité lies à leur utilisation comme molécules cosmétiques. Abbreviated : Biopolymers offer a wide range of advantages that, properly applied, can have a huge impact on new cosmetic trends. This review focuses on polysaccharide‐ and protein‐based biopolymers, describing sources of obtention, newly derived molecules, trends in cosmetic products and safety aspects.